PENGARUH KEMASAN, KUALITAS, MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SAMPO PANTENE PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS SUMATERA UTARA - windi yulisa zulkarnain; ulfah ulfah (Universitas Sumatera Utara, 2013)
Abstract This research aims to determine and analyze the influences packaging, quality, branding and price for purchasing decision of shampoo Pantene on Faculty of Economic University of North Sumatera’s students. Sampling technique using a purposive sampling method. With target of 97 population are Faculty of Economic University of North Sumatera’s students who had purchased and using shampoo Pantene. This research using data by questionnaire and documentation. Measured data using Likert scale. Data processing with hypothesis testing using linier regresion analysis. The results of this research showed quality and branding have a positive and significant effect for purchasing decision of shampoo Pantene on Faculty of Economic University of North Sumatera’s students but packaging and price have a positive but not significant effect for purchasing decision of shampoo Pantene on Faculty of Economic University of North Sumatera’s. Rated R sequare = 59,6% mean that relation of variabel tight enough. Keywords: Consumer Involvement, Differences inter Brands, Buying Decision